Radiation treatment compliance in the Indigenous population: The pilot Northern Territory experience and future directions. Issue 2 (26th March 2013) - Le, Hien; Penniment, Michael; Carruthers, Scott; Roos, Daniel; Sullivan, Thomas; Baxi, Siddhartha
Abstract Introduction There is a perception that Indigenous patients are less likely to attend radiotherapy treatment. This study sought to determine if a difference in radiotherapy treatment compliance rates exists between Indigenous and non‐Indigenous patients. Secondly, we aimed to ascertain which patient, disease and treatment factors affect compliance in Indigenous patients. Methods All patients treated with radiotherapy at the Alan Walker Cancer Care Centre between March and October 2010 were analysed. Data regarding compliance rates (defined as those who chose and completed the recommended course of treatment), patient, disease and treatment factors were collected, and chi‐squared and Fisher's exact tests were applied. Results A total of 41 courses were delivered to Indigenous patients and 224 courses delivered to non‐Indigenous patients in this period. There was no difference in compliance between Indigenous and non‐Indigenous patients (83% vs. 81%, P = 0.75). Of the factors assessed, it was found that there was an association between toxicity grade and compliance (P = 0.048). Conclusions From this cohort, we cannot support the perception that Indigenous patients have overall poorer compliance with recommended radiation treatment courses. In this study, the only factor which correlated significantly with compliance was toxicity grade. It is felt that a number of factors, which negatively impact on compliance, can potentially be counteracted by a culturally sensitive model of care.